SAT0330 VALUE OF DIAPHRAGMATIC ASSESSMENT IN RELATION TO PULMONARY FUNCTIONS AND DISEASE ACTIVITY IN AXIAL SPONDYLOARTHROPATHIES: PRELIMINARY REPORT. (June 2019) - Güneş, Seçilay; Genç, Aysun; Sunar, İsmihan; Özdemir, Sevgi Esra; Gökmen, Derya; Ataman, Şebnem; Aytür, Yesim Kurtais
Abstract : Background: Axial Spondyloarthropathies (SpA) are chronic, systemic, inflammatory diseases which affect the axial skeleton, limit chest mobility and cause serious impairments in pulmonary functions. Objectives: In this cross-sectional study, as a new approach; diaphragm thickness is assessed by ultrasound in patients with axial SpA to determine possible relationships with pulmonary functions and disease activity. Methods: 49 axial SpA patients enrolled in the study were assessed by Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Ankylosing Spondylitis Metrology index (BASMI), Erythrocyte Sedimentation Rate (ESR), serum C-Reactive Protein levels (CRP) and chest expansion (cm). 15 patients with lung diseases other than axial SpA pulmonary involvement, neuromuscular diseases, scoliosis and congenital chest deformity were excluded. Dynamic pulmonary function tests (PFT) and 6 min walk (6MW) tests were done and physical activity levels were evaluated by short form International Physical Activity Questionnaire (IPAQ). Diaphragm thickness was measured at end expiration (dtFRC) and deep inspiration (total lung capacity (dtTLC)). Thickness ratio (dtr: dtTLC/dtFRC) and thickness change (dtc: dtTLC-dtFRC) were calculated. Results: The descriptive data of the patients are presented in Table 1 . Patients had a moderate disease activity and all the patients were category 1 (inactivity) according to IPAQ. Mean value of dtr and PFT seem to be within normal range according to population studies and dtr was significantly correlated with dynamic pulmonary function tests, yet negatively correlated with ESR (r: -0.466, p: 0.006). There was insignificant negative correlation with age, disease duration, BASDAI, BASFI, and BASMI. Conclusion: To the best of our knowledge, this is the first study evaluating the relation between diaphragm thickness and pulmonary functions with disease activity. Even though, there was no limitation in PFT and expected values were obtained in dtr, the negative correlation with ESR makes us think about the possible effect of disease activity on dtr. With these preliminary results, it is early to conclude, but dtr assessment may be complementary to PFT and early measures to improve diaphragm function with specific exercises should be implemented in patients with axial SpA. Reference: [1] Carrillo-Esper R, Pérez-Calatayud ÁA, Arch-Tirado E, Díaz-Carrillo MA, Garrido-Aguirre E4, Tapia-Velazco R, Peña-Pérez CA, Espinoza-de Los Monteros I, Meza-Márquez JM, Flores-Rivera OI, Zepeda-Mendoza AD, de la Torre-León T. Standardization of Sonographic Diaphragm Thickness Evaluations in Healthy Volunteers Respir Care 2016;61(7):920-4 Disclosure of Interests: None declared